Evaluation of the attitudes, actions, and preferences of pharmacists about ongoing education - alshotairy, Ahmed ayed Hamadan; Almutiri , Alhnouf; Qohal , Abdulaziz Abdullah; al enami, Abdulellah mansor; Al- shatari, Fahad Ayed; bukhari, Mohammed Nouraldeen Shamsaldeen; Gashgari, Mahmoud Saleem; ALharbi, Rajih Radi; Al summan, Khaled muith (Journal of Ecohumanism, 2024)
Background: Pharmaceutical care is a dynamic field that requires continuous education (CE) to ensure pharmacists remain proficient in addressing advancements in healthcare. Understanding pharmacists’ attitudes, actions, and preferences toward CE is crucial for designing effective programs that align with their needs and overcome barriers to participation. Methods: A cross-sectional study was conducted among 500 licensed pharmacists using a structured, self-administered questionnaire. Participants were recruited from various practice settings, including community pharmacies, hospitals, academia, and medical representatives. The survey assessed demographic characteristics, attitudes toward CE, participation frequency, preferred learning methods, and barriers to engagement. Data were analyzed using descriptive and inferential statistics, including multivariate logistic regression to identify predictors of positive attitudes and high CE participation. Results: Of the participants, 78% strongly agreed or agreed that CE is essential for professional development. Common barriers to participation included time constraints (62%), lack of access to quality programs (45%), and financial limitations (30%). Preferred CE formats were online courses (65%) and workshops (50%), with high interest in clinical practice topics (82%), drug safety (58%), and pharmacy management (40%). A significant association was observed between professional roles and preferences for CE formats and topics (p < 0.05). Conclusion: Pharmacists strongly value CE for professional growth, favoring flexible and workplace-relevant learning formats. Addressing barriers such as time, cost, and access to quality programs is critical to enhancing participation. Future CE initiatives should include routine needs assessments and offer diverse, cost-effective, and practical learning opportunities tailored to pharmacists’ professional roles and preferences.